Electronic dictionary for Herb’s plant - Foo Yee Mei (Universiti Malaysia Perlis, 2008)
Biotechnology is recently been given particular attention to the researchers in Malaysia. The growth of biotechnology field is increased robustly nowadays. Among the species, the herb’s species is very potential in biotechnology research area for food and medicine industry. Malaysia is enriched with a variety of herb’s species. But, most of these precious plant species data are not well managed. Some of the database is even stored in a PC, which is very bulky and power hungry. So, it is not suitable for the Biotechnology researches in the field. To overcome this problem, a high performance device of electronic dictionary for herb’s plant is designed. The device is designed by using FPGA. The FPGA is suitable because of its high speed and parallel data processing. It is also definitely suitable for mobile application. The control unit of electronic dictionary consists of an FPGA chip as a main processing unit, a memory module, LCD panel as a output display unit and a keypad as the input. VHDL is used to define the FPGA functional unit in Quartus II. The new devices are helpful and useful to simplify control and modify operating speed of a microprocessor managing its peripheral devices.